Effects of the binding of a Helianthus annuus lectin to Candida albicans cell wall on biofilm development and adhesion to host cells - del Rio, Marianela Victoria (2019)
Background: In our previous study, we isolated and characterized a lectin called Helja from Helianthus annuus (sunflower) and then, in a further study, demonstrated its antifungal activity against Candida spp. Since Candida infections are a major health concern due to the increasing emergence of antifungal resistant strains, the search for new antifungal agents offers a promising opportunity for improving the treatment strategies against candidiasis. Purpose: The aim of this work was to get insights about the mechanism of action of Helja, an antifungal lectin of H. annuus, and to explore its ability to inhibit Candida albicans biofilm development and adherence to buccal epithelial cells (BEC). Study design/methods: Yeast viability was evaluated by Evans Blue uptake and counting of colony forming units (CFU). The yeast cell integrity was assessed using Calcofluor White (CFW) as a cell wall perturbing agent and sorbitol as osmotic protectant. The induction of oxidative stress was evaluated using 3,3′-diaminobenzidine (DAB) for detection of hydrogen peroxide. The adherence was determined by counting the yeast cells attached to BEC after methylene blue staining. The biofilms were developed on polystyrene microplates, visualized by confocal laser scanning microscopy and the viable biomass was quantified by CFU counting. The binding lectin-Candida was assessed using Helja conjugated to fluorescein isothiocyanate (Helja-FITC) and simultaneous staining with CFW. The cellular surface hydrophobicity (CSH) was determined using a microbial adhesion to hydrocarbons method. Results: C. albicans cells treated with 0.1 µg/µl of Helja showed a drastic decrease in yeast survival. The lectin affected the fungal cell integrity, induced the production of hydrogen peroxide and inhibited the morphological transition from yeast to filamentous forms. Helja caused a significant reduction of adherent cells and a decrease in biofilm biomass and coverage area. The treatment with the protein also reduced the surface hydrophobicity of fungal cells. We show the binding of Helja-FITC to yeast cells distributed as a thin outer layer to the CFW signal, and this interaction was displaced by mannose and Concanavalin A. Conclusion: The results demonstrate the interaction of Helja with the mannoproteins of C. albicans cell wall, the disruption of the cell integrity, the induction of oxidative stress, the inhibition of the morphological transition from yeast to filamentous forms and the fungal cell viability loss. The binding Helja-Candida also provides a possible explanation of the lectin effect on cell adherence, biofilm development and CSH, relevant features related to virulence of the pathogen.